Carbonate apatite nanoparticles carry siRNA(s) targeting growth factor receptor genes egfr1 and erbb2 to regress mouse breast tumor - Snigdha Tiash; Nur Izyani Binti Kamaruzman; Ezharul Hoque Chowdhury (Taylor & Francis Group, 2017)
Cancer cells lose their control on cell cycle by numerous genetic and epigenetic alterations. In a tumor, these cells highly express growth factor receptors (GFRs), eliciting growth, and cell division. Among the GFRs, epidermal growth factor receptor-1 (EGFR1) (Her1/ERBB1) and epidermal growth factor receptor-2 (EGFR2) (Her2/ERBB2) from epidermal growth factor (EGF) family and insulin-like growth factor-1 receptor (IGF1R) are highly expressed on breast cancer cells, thus contributing to the aggressive growth and invasiveness, have been focused in this study. Moreover, overexpression of these receptors is related to suppression of cell death and conferring resistance against the classical drugs used to treat cancer nowadays. Therefore, silencing of these GFRs-encoding genes by using selective small interfering RNAs (siRNAs) could be a powerful approach to treat breast cancer. The inorganic pH sensitive carbonate apatite nanoparticles (NPs) were used as a nano-carrier to deliver siRNA(s) against single or multiple GFR genes in breast cancer cells as well as in a mouse model of breast carcinoma. Silencing of egfr1 and erbb2 simultaneously led to a reduction in cell viability with an increase in cell death signal in the cancer cells and regression of tumor growth in vivo.